Old and new pathogenic Nakaseomyces species: epidemiology, biology, identification, pathogenicity and antifungal resistance. Issue 2 (20th December 2015) - Angoulvant, A.; Guitard, J.; Hennequin, C.
Abstract : During the previous decades, as the number of immunocompromised patients, the average age of Western populations and the widespread use of indwelling medical devices have increased concomitantly, so has the incidence of infections caused by Candida species. Candida albicans remains the most frequently isolated agent of candidiasis. However, C. glabrata now accounts for a substantial part of clinical isolates, ranking number two among the etiologic agents of either superficial or invasive candidiasis in North America and Europe. Along with C. glabrata and belonging to the Nakaseomyces clade, two new species, C. nivariensis and C bracarensis have recently been described as emerging pathogens. This review provides information on the current state of knowledge on the epidemiology, biology, identification, pathogenicity and antifungal resistance of C. glabrata, C. nivariensis and C. bracarensis. Abstract : This review provides the current state of knowledge on the epidemiology, biology, identification, pathogenicity and antifungal resistance of C. glabrata, C. nivariensis and C. bracarensis .